Citizens in a strange land : a study of German-American broadsides and their meaning for Germans in North America, 1730-1830 - Wellenreuther, Hermann (Max Kade German-American Research Institute, 2013)
In Citizens in a Strange Land, Hermann Wellenreuther examines the broadsides—printed single sheets—produced by the Pennsylvania German community. These broadsides covered topics ranging from local controversies and politics to devotional poems and hymns. Each one is a product of and reaction to a particular historical setting. To understand them fully, Wellenreuther systematically reconstructs Pennsylvania's print culture, the material conditions of life, the problems German settlers faced, the demands their communities made on the individual settlers, the complications to be overcome, and the needs to be satisfied. He shows how these broadsides provided advice, projections, and comment on phases of life from cradle to grave.